Single Photon vs Two Photon Excitation of Silver Nanocluster. Issue 1 (March 2020) - Tripathy, J.; Lu, Y-H; Islam, Md. S.; Dickson, R. M.
Abstract: Silver nanodots, nanoparticles and nanoclusters have been of immense interest to researchers for some time now. A lot has been published in this field from synthesis to optical properties of various types of silver nanoclusters. In this work we explore the impact of polarized excitation on modulatability and fluorescence enhancement of silver (Ag) nanocluster. Ag nanoclusters as previously reported are enhancible and modulatable, however, for pathological application purposes emission in NIR even IR is desirable, so that the fluorescence signal detection over the auto-fluorescence background signal in vivo mode becomes easier. In a preliminary work we have seen a rise in anisotropic values beyond the maximum steady state anisotropy of 0.4 when the sample is excited using two colored laser light. Though there are numerous multi-photon study results available in literature, this is first of its kind where we use two polarized excitations to sequentially probe the excitable dark state of the cluster and the emission is then analyzed to obtain a value of steady state anisotropy along with changes observed in signal enhancement owing to modulation of the secondary excitation source. Ag nanocluster samples encapsulated by 10- or 12-mer ss-DNA capable of producing red to NIR light upon excitation at shorter wavelengths were prepared in-house.